Hubungan Tingkat Stres Dengan Timbulnya Jerawat Pada Siswa Smp Negeri 4 Ngawi - , Ika, Prof. Dr. Mohammad Fanani, dr. Sp. Kj (K), Dr. Erna Herawati, Sp.K.J (2015)
Background: Acne vulgaris, or it is usually called as acne, is an obstructive and chronic inflammatory skin disease of pilocebacea and it is often occurring in adolescence, mostly in male of 14-15 years old. The cause of acne onset is multifactor, and one of them is psychological stress. Purpose: Purpose of the research is to know correlation between stress level and acne onset among at student's SMP Negeri 4 Ngawi. Method: The research uses an observational-analytic method with cross-sectional approach. Spearman test is used to know significance of correlation between the two variables. Results: It was found that 68.3% of 41 students suffered from stress and the affected students had acne with mild, moderate and serious degrees of severity. There is correlation between stress level and acne onset of male at student's SMP Negeri 4 Ngawi (p < 0.001). Conclusion: There is a very significant and positive correlation between stress level and acne onset among male students of SMP Negeri 4 Ngawi, increasingly high stress levels the high arise acne.